E-Business Management as an Approach to Improve the Quality of Educational Services at Palestinian Universities: A Case Study of Al-Azhar University of Gaza - Soha Esam Meghari; Raghda Mahmoud El Ngeli; Mervat M.M. Rady (University of Science and Technology, Yemen, 2018)
This study aimed to identify how far Al-Azhar University applies e-business management and achieves quality of educational services. It also intended to examine the influence of e-business (planning, organization, direction, and control) on the quality of educational services. The study also aimed to identify significant differences among the participants' responses with regard to the influence of e-business on the quality of educational services due to position, education, and experience. The study population consisted of all the university employees (except service staff) which were (570) employees. The study sample was randomly selected. 138 questionnaires were distributed, of which 120 questionnaires were investigated for the purpose of this study. The study concluded with the following findings: The level of e-business management implementation was weak at the university. There was a positive relationship between e-business management and the quality of educational services. There were no significant differences in the participants' responses with regard to the influence of e-business on the quality of educational services due to position. However, there were significant differences attributed to education and experience. Keywords: E-business management, Quality of educational services, Electronic planning.